Evaluation of Allicin as Soil Urease Inhibitor - Mathialagan, R. (Elsevier Ltd, 2017)
Urea is the most widely used form of N fertilizer in agriculture. However, if it is not incorporated into soil soon after application, urea has the disadvantage of undergoing considerable losses as ammonia gas due to hydrolysis in the presence of soil urease. Urease inhibitors are some of the most commonly used approaches to overcome nitrogen losses in fields, as they delay urea hydrolysis and thus increase the chances of urea incorporation into soil. Among the known soil urease inhibitors is the chemical based N(butyl) thiophosphoric triamide (NBPT) but it is found to cause some phytotoxic effect on plants among assimilation issues. Allicin, a natural based bio-inhibitor from garlic (Allium sativum L.), has shown potential to inhibit urease activity. In this context, laboratory experiments were conducted to examine the effect of different allicin concentrations on soil urease inhibition period. The loss of applied urea was quantified, using diacetylmonoxime (DAM) calorimetric method, following application of urea with and without allicin. Urea and a mixture of urea and allicin at different concentrations (5, 10 and 15 w allicin/w urea) were surface-applied at a rate of 1000 μg Urea N/kg soil to small circular containers. The soil was irrigated to maintain the moisture content between 25-30 throughout the study. This study suggest that prilled form urea application gave more consistent results than when urea was dissolved and added to the soil as a solution. Through this study, it was shown that allicin exerts inhibitory effects on urease in soil for agricultural applications, where 5 weight allicin to weight urea applied resulted in the best urease inhibition. At the given operating parameters, allicin inhibition was about 75 less than NBPT at steady state. While this study demonstrated the potential of allicin as a viable bio-inhibitor to retard the loss of urea in soil and thus it may be used along with urea for improved utilization of the applied -N by plants. © 2017 The Authors.